Review of qualitative experimental methods for visualising airflow around aircraft mock-ups in wind tunnels - Eliza-Ioana Apostol; Aurel Mihail Țîțu (Journal of Research and Innovation for Sustainable Society)
Around aerodynamic models in the subsonic tunnel, there are several qualitative experimental methods of visualising airflow that can provide valuable information about their aerodynamic behaviour. These methods allow researchers to visualise how air moves around the model and to observe complex phenomena such as flow separation. These qualitative experimental methods of visualising airflow provide a visual understanding of aerodynamic behaviour and allow researchers to identify and analyse complex phenomena that occur around aerodynamic models in the subsonic tunnel. By using these methods, valuable data is obtained that can be used to improve aerodynamic design and develop advanced technologies